Impella RP as a bridge to cardiac transplant for refractory late right ventricular failure in setting of left ventricular assist device. (19th May 2020) - Randhawa, Varinder Kaur; Hoffman, Karlee; Bock, Ashley; Bhat, Pavan; Young, Laura; Rossi, Jeffrey; Campbell, Joseph; Bott‐Silverman, Corrine; Soltesz, Edward G.; Tong, Michael Z.Y.; Unai, Shinya; Nair, Ravi; et al.
Abstract: Right ventricular (RV) failure remains a major complication after surgical implantation of a left ventricular assist device (LVAD). While the use of a percutaneous RV assist device has been described as a short‐term bridge to recovery in end‐stage heart failure patients with early post‐operative RV failure after index LVAD implant, management of refractory late RV failure remains challenging in these patients. We report the first successful case of extended Impella RP use as a safe and effective bridge to orthotopic heart transplant in an LVAD patient with refractory, haemodynamically significant late RV failure. The Impella RP provided support for 37 days. Haemodynamically intolerant arrhythmia precluded use of inotropic support. No adverse complications related to percutaneous Impella RP support were seen. We also review potential considerations for mechanical circulatory support strategies in this setting: central RV assist device cannulation requires sternotomy incision that can impact subsequent cardiac surgeries, while percutaneous Protek Duo insertion requires adequate vessel size and patency. With an LVAD in situ, veno‐arterial extracorporeal membrane oxygenation was not considered for isolated RV support in this case. The patient is currently over 6 months post‐orthotopic heart transplant.